Nonpregnant and pregnant adult female rats affected by maternal diabetes environment - Paula, Veronyca Goncalves [UNESP]; Souza, Maysa Rocha de [UNESP]; Sinzato, Yuri Karen [UNESP]; Villaverde, Ana Izabel Silva Balbin [UNESP]; Corrente, Jose Eduardo [UNESP]; Volpato, Gustavo Tadeu; Damasceno, Débora Cristina [UNESP] (Taylor & Francis Inc, 2022)
Maternal diabetes-mediated fetal programming is widely discussed, however, it is important to define the extent to which intrauterine hyperglycemia interferes with the health of female pups, along with determining whether these changes can be perpetuated across generations. This study aimed to evaluate the effects of maternal diabetes on fetal programming and the repercussions on the metabolism of pregnant and nonpregnant female pups. Diabetes status was induced (diabetic group-D) using streptozotocin (a beta cell cytotoxic drug) on the fifth postnatal day of female rats, while controls received a citrate buffer (Control-C). In adulthood, the rats were mated to obtain their female pups. At 90 days of age, half of the female pups were mated (preg) and the other half continued virgin (Npreg). Furthermore, they were distributed into four groups: OC/Npreg and OC/preg-female pups from control mothers; OD/Npreg and OD/preg-female pups from diabetic mothers. At 115 days of life and/or 17 days of pregnancy, the oral glucose tolerance test (OGTT) was performed with blood collection for insulin measurement. At 120 days of life and/or 21 days of pregnancy, the rats were anesthetized and euthanized to determine their blood oxidative stress status. The OD/Npreg group showed glucose intolerance during OGTT (p < 0.0001), while the OD/preg group showed increased insulin secretion during OGTT (p < 0.0001) and insulin resistance (IR; p = 0.0027). An increase in homeostatic model assessment beta was shown in the pregnant groups, regardless of maternal diabetes (p < 0.0001). The OD/preg group presented increased thiobarbituric acid reactive substances (p < 0.0001) and -SH levels (p = 0.0005) and decreased superoxide dismutase activity (p = 0.0063). Additionally, small fetuses for gestational age (p < 0.0001) were found in these rats. In conclusion, exposure to maternal hyperglycemia compromises the glycemic metabolism of female pups before and during pregnancy and causes oxidative stress, IR, and impaired fetal growth during pregnancy.
Keywords: Fetal programming; Hyperglycemia; Oxidative stress; Insulin resistance; Low birth weight